Effects of lorcaserin on fat and lean mass loss in obese and overweight patients without and with type 2 diabetes mellitus: the BLOSSOM and BLOOM‐DM studies. Issue 9 (22nd June 2016) - Apovian, C.; Palmer, K.; Fain, R.; Perdomo, C.; Rubino, D.
Abstract : Body composition was determined using dual‐energy X‐ray absorptiometry (DXA) in a subset of patients without (BLOSSOM) and with (BLOOM‐DM) type 2 diabetes who received diet and exercise counselling along with either lorcaserin 10 mg twice daily or placebo. DXA scans were performed on study day 1 (baseline), week 24 and week 52. Baseline demographics of the subpopulations (without diabetes, n = 189; with diabetes, n = 63) were similar between studies and representative of their study populations. At week 52, patients without diabetes on lorcaserin lost significantly more fat mass relative to those on placebo (−12.06% vs −5.93%; p = 0.008). In patients with diabetes, fat mass was also decreased with lorcaserin relative to placebo (−9.87% vs −1.65%; p < 0.05). More fat mass was lost in the trunk region with lorcaserin compared with placebo (without diabetes: −3.31% vs −2.05%; with diabetes: −3.65% vs −0.36%). Weight loss with lorcaserin was associated with a greater degree of fat mass loss than lean mass loss, and most of the fat mass lost for patients without and with diabetes was from the central region of the body.